Management of Rice Farming Production Factors Nutrizinc Inpari 48 Farmers Group “Ngudi Makmur - Andajani, Wiwiek; Lisanty, Nina; Andarini, Marwita; Chumaidah, Siti (Universitas Djuanda, 2024)
Public health is essential for the resilience of Indonesian society, especially for future generations, and meeting nutritional needs. Rice (paddy), a staple food for Indonesians, plays a crucial role in human health. Ensuring its safety and nutritional value requires attention to the entire production process, from seed selection, cultivation, and plant maintenance to harvest and post-harvest handling. Given the high prevalence of malnutrition and stunting, the government has initiated programs to address these issues. In 2019, the Ministry of Agriculture introduced Inpari IR Nutri Zinc, a new rice variety rich in iron and zinc, to combat these problems. The research aimed to (1) determine the feasibility of farming this variety and (2) assess the efficiency of production factor usage in Nutrizinc Inpari 48 rice farming. This quantitative study, with a descriptive approach, was conducted through a survey, intentionally selecting the